Immunomodulatory Pathways of Some Biomarkers in Individuals with Renal Failure - Shallal, Ahmed F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This study investigates the correlation between renal failure and immunoinflammatory marker pathways. Specimens were obtained from the Hemodialysis Center located in the cities of Ranya and QaladezeSulaymaniyah, KRG, Iraq. The investigation included a well-defined cohort of 120 individuals (60 patients and 60 control participants), comprising both sexes, during the period from October to December 2024. Participants ranged in age from 40 to 60 years. The concentrations of immunoglobulins (IgA, IgM, and IgG) were measured using the Cobas 6000 analyzer, while IgE levels were assessed with the Cobas e 411 analyzer. The enzyme-linked immunosorbent assay was utilized for detecting the variations of cytokines (Tumor necrosis factor-alpha, interleukin (IL)-6, and IL-10) and antinuclear antibody (ANA). Erythrocyte sedimentation rate (ESR) was determined using the automated ESR analyzer. Individuals diagnosed with end-stage renal disease (ESRD) exhibited significant immunological alterations, marked by a significant decrease in IgA, IgM, and IgG levels and accompanied by a substantial elevation in IgE levels. The current investigation revealed a markedly elevated ESR, tumor necrosis factor- alpha (TNF-α), IL-6, and IL-10 in reference to the healthy subjects. ANA titers exhibited a slight increase within the patient population. This immunological dysregulation is further associated with elevated levels of TNF-α, IL-6, and IL-10, indicating a persistent systemic inflammatory state. The synchronous augmentation of ESR and TNF-α and IL-6 confirms their potential utility as prognostic biomarkers for chronic inflammation in ESRD patients. Observation of elevated inflammatory markers in females indicates a potential gender-specific variation in immune response pathways within this clinical population.